Determinants of Impulse Buying in Digital Marketplaces: The Roles of Celebrity Endorsement, Online Reviews, and Shopping Lifestyle - Nenik Diah Hartanti; Hendri Rahmayani Asri; Ekaning Setyarini; Budi Santoso; Hantoro Arief Gisijanto (Lentera Ilmu Nusantara, 2025)
The purpose of this study is to analyze the influence of celebrity endorsement , online customer review and shopping lifestyle on impulse buying partially and simultaneously of marketplace users. The analysis method in this study uses primary data processed using SPSS, with the analysis techniques used are validity test, reliability test, classical assumption test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, hypothesis test, partial test (t test), simultaneous test (f test), coefficient of determination test (R2) . The data used in this study were obtained from questionnaires and valid data collected from 100 respondents. The sampling method in this study is non-probability sampling with a sampling technique using purposive sampling. The population in this study was marketplace users. The results of this study indicate that celebrity endorsement variables have no effect on impulse buying among marketplace users, while online customer reviews and shopping lifestyle variables have a partial effect on impulse buying. Simultaneously, celebrity endorsement, online customer reviews, and shopping lifestyle variables influence impulse buying among marketplace users.